Pharmacological properties of dicyanidoaurate(I)-based complexes: characterization and single crystal X-ray analysis - Karadag, Ahmet; Aydin, Ali; Tekin, Saban; Akbas, Huseyin; Dede, Sureyya (TAYLOR & FRANCIS LTD, 2019)
AbsractThe synthesis of three bimetallic cyanido complexes with edbea [2,2-(ethylenedioxy)bis(ethylamine)] ligand is reported. [Ni-II(-edbea)(2){Au(-CN)(2)}(2)](n) (1), [{Cu-II(edbea)}(2){Au(-CN)(2)}(4)](n) (2) and [Cd-II(edbea)(2)][Au(CN)(2)](2)H2O (3) were fully characterized by elemental, infrared, XRD (3), ESI-MS and thermal analysis. The DNA/BSA binding properties of these complexes were evaluated by spectrophotometric titration, fluorometric ethidium bromide kinetics, and DNA electrophoresis studies and their partially minor groove binding mode between the base pairs of DNA and electrostatic interaction between the amino acid residues of BSA were explained. The complexes were tested for their pharmacological properties. These molecules had excellent in vitro antiproliferative activity and also exhibited a strong tumor inhibiting effect against HT29, HeLa, C6 and Vero cell lines. These complexes had metastatic features as they are able to reduce cell migration activity and suppress tumor growth in vitro. Analysis of the DNA topoisomerase I relaxing activity indicates that the complexes do not inhibit topoisomerase I which regulates the topological states of the DNA double helix during DNA processing reactions. The TUNEL and DNA laddering assay results indicated that these compounds may destroy cell maintenance by triggering apoptosis. Immunohistochemistry staining analysis demonstrated that these complexes significantly decreased the expression of Bcl-2 in HeLa and HT29 cells while increasing the expression of P53 levels. Overall, the potent antiproliferative activity, low cytotoxic effect, good solubility, and micro molar range dosage observed for these complexes emphasizes their potential as anticancer drug candidates. [GRAPHICS] .
Keywords: 2,2'-(Ethylenedioxy)bis(ethylamine); dicyanidoaurate(I); antiproliferative activity; apoptosis; IN-VITRO; COORDINATION POLYMERS; ANTICANCER ACTIVITIES; GOLD COMPLEXES; CANCER CELLS; INTERPLAY; DICYANIDOARGENTATE(I); MECHANISM; CISPLATIN; COMPOUND; Chemistry